Using a period incidence survey to compare antibiotic use in children between a university hospital and a district hospital in a country with low antimicrobial resistance: a prospective observational study - Christian Magnus Thaulow; Hege Salvesen Blix; Beate Horsberg Eriksen; Ingvild Ask; Tor Åge Myklebust; Dag Berild (BMJ Open, 2019)
ObjectivesTo describe and compare antibiotic use in relation to indications, doses, adherence rate to guidelines and rates of broad-spectrum antibiotics (BSA) in two different paediatric departments with different academic cultures, and identify areas with room for improvement.DesignProspective observational survey of antibiotic use.SettingPaediatric departments in a university hospital (UH) and a district hospital (DH) in Norway, 2017. The registration period was 1 year at the DH and 4 months at the UH.Participants201 children at the DH (mean age 3.8: SD 5.1) and 137 children at the UH (mean age 2.0: SD 5.9) were treated with systemic antibiotics by a paediatrician in the study period and included in the study.Outcome measuresMain outcome variables were prescriptions of antibiotics, treatments with antibiotics, rates of BSA, median doses and adherence rate to national guidelines.ResultsIn total, 744 prescriptions of antibiotics were given at the UH and 638 at the DH. Total adherence rate to guidelines was 75% at the UH and 69% at the DH (p=0.244). The rate of treatments involving BSA did not differ significantly between the hospitals (p=0.263). Use of BSA was related to treatment of central nervous system (CNS) infections, patients with underlying medical conditions or targeted microbiological treatment in 92% and 86% of the treatments, at the UH and DH, respectively (p=0.217). A larger proportion of the children at the DH were treated for respiratory tract infections (p<0.01) compared with the UH. Children at the UH were treated with higher doses of ampicillin and cefotaxime (p<0.05) compared with the DH.ConclusionOur results indicate that Norwegian paediatricians have a common understanding of main aspects in rational antibiotic use independently of working in a UH or DH. Variations in treatment of respiratory tract infections and in doses of antibiotics should be further studied.